Catastrophic antiphospholipid syndrome as a complication of systemic sclerosis - D.J. Manzella (Reumatismo, 2019)
A 62-year-old man with a history of systemic sclerosis was admitted with diffuse alveolar hemorrhage and acute kidney injury without clinical data suggestive of glomerulonephritis. Laboratory tests showed anemia, leukocytosis with neutrophilia, thrombocytopenia, elevated serum creatinine and metabolic acidosis. Antinuclear antibodies were positive at a titer of 1/640 (speckled, 1/160; nucleolar, 1/320) while rheumatoid factor, anti Scl-70, anti-centromere, anti-neutrophil cytoplasmic antibody and anti-glomerular basement membrane antibodies were negative and serum complement levels were within normal range. During the following days, the patient developed multiple organ failure and, eventually, died. Lupus anticoagulant was revealed positive after the patient’s death, suggesting a catastrophic antiphospholipid syndrome. Clinical data and autopsy were consistent with this diagnosis.